Olfactory stimulation Inhibits Nociceptive Signal Processing at the Input Stage of the Central Trigeminal System. (15th December 2021) - Papotto, Nunzia; Reithofer, Sara; Baumert, Kaya; Carr, Richard; Möhrlen, Frank; Frings, Stephan
Highlights: Noxious stimulation induces network activity in the spinal trigeminal nucleus. In mice, this network activity leads to pain perception and avoidance behavior. Olfactory co-stimulation reduces network activity and nocifensive behavior. Stimulation with odorants can reduce trigeminal pain processing. Abstract: The spinal trigeminal nucleus caudalis (SpVc) in the mammalian brainstem serves a pivotal function in pain processing. As the main relay center for nociceptive signals, SpVc conducts pain-related signals from various regions of the head toward higher levels of central processing such as the thalamus. SpVc also receives modulatory signals from other brain areas, which can alleviate the perception of headache. We studied the impact of olfactory co-stimulation on pain-related behavior and SpVc neural activity in mice. Using the TRPA1 agonist allyl isothiocyanate (AITC) as noxious stimulus, we quantified the aversive response and the perceived pain intensity by evaluating explorative running and the mouse grimace scale, respectively. We found that the floral odorants phenylethyl alcohol (PEA) and lavender oil mitigated the aversive response to AITC. Consistent with this finding, a newly developed, automated quantification of c-Fos expression in SpVc revealed that co-stimulation with PEA or lavender profoundly reduced network activity in the presence of AITC. These results demonstrated a substantial analgesic potential of odor stimulation in the trigeminal system and provide an explanation for the palliative effect of odors in the treatment of headache.